2011
DOI: 10.3389/fcimb.2011.00010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Recombinant B. abortus Strain RB51SOD Toward Understanding the Uncorrelated Innate and Adaptive Immune Responses Induced byRB51SOD Compared to Its Parent Vaccine Strain RB51

Abstract: Brucella abortus is a Gram-negative, facultative intracellular pathogen for several mammals, including humans. Live attenuated B. abortus strain RB51 is currently the official vaccine used against bovine brucellosis in the United States and several other countries. Overexpression of protective B. abortus antigen Cu/Zn superoxide dismutase (SOD) in a recombinant strain of RB51 (strain RB51SOD) significantly increases its vaccine efficacy against virulent B. abortus challenge in a mouse model. An attempt has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…One possible explanation is that Brucella vaccines may not effectively penetrate into mucosal physical barriers ( e.g ., nose). Therefore, Brucella antigens cannot efficiently be presented to the antigen presenting cells, including dendritic cells and macrophages [39]. …”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation is that Brucella vaccines may not effectively penetrate into mucosal physical barriers ( e.g ., nose). Therefore, Brucella antigens cannot efficiently be presented to the antigen presenting cells, including dendritic cells and macrophages [39]. …”
Section: Discussionmentioning
confidence: 99%
“…Zhu, et al has reported that overexpressed Cu-Zn SOD protein by Brucella vaccine strain RB51 damages the integrity of the outer membrane of RB51 Brucella cells [ 4 ]. To determine if secretion of Cu-Zn SOD protein in B. abortus 2308 results from leakage of damaged outer membranes, we investigated membrane integrity with transmission electron microscope analysis of wild type B. abortus 2308 and 2308 overexpressing Cu-Zn SOD.…”
Section: Resultsmentioning
confidence: 99%
“…Another important finding of this study is that overexpressed Cu-Zn SOD inhibits B. abortus intracellular growth via suppressing the activity of the small GTpase protein Sar1. Previous study showed that macrophages infected with Brucella RB51 Cu-Zn SOD strain exhibited a significantly lower number of surviving cells than RB51 strains [ 4 ]. However, the underlying mechanism remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations